Application of intuitive fuzzy MABAC method in optimizing favorable areas of low permeability carbonate gas reservoirs - MIN Chao,LI Yingjun,LI Xiaogang,HUA Qing,ZHANG Na (Youqicang pingjia yu kaifa)
The geological structure and reservoir characteristics of low-permeability carbonate gas reservoirs are complex, and the high uncertainty in data acquisition and interpretation makes it challenging to identify optimal development areas. To address this, the study introduces an intuitionistic fuzzy Multi-Attributive Border Approximation area Comparison（MABAC） model, combined with the Best Worst Method（BWM） for weighting, to select the most suitable areas for developing these reservoirs. The approach begins by establishing a comprehensive evaluation index system that considers geological characteristics, hydrocarbon generation capacity, and gas storage capability of the low-permeability carbonate formations. This system not only integrates geological data but also considers the construction conditions relevant to these reservoirs. Using the BWM, weights for each key evaluation indicator are determined, taking into account the multifactorial impacts on various oil and gas fields and establishing the hierarchical relationships between these factors. An improved intuitionistic fuzzy multi-attribute decision-making model is then developed. This model uses intuitionistic fuzzy data instead of precise information, enhancing the selection process for favorable areas. The application of this model on ten candidate blocks indicated that Block C is the most favorable, outperforming others in terms of remaining dynamic reserves, effective reservoir thickness, and other crucial indicators. The blocks were ranked as follows based on the overall distance value: Block C > Block I > Block H > Block A > Block D > Block G > Block J > Block E > Block F > Block B. The effectiveness and rationality of the proposed intuitionistic fuzzy MABAC method were validated through comparisons with existing methods and analysis of numerical simulation results, confirming its utility in optimizing the development of low-permeability carbonate gas reservoirs.